Effects of foot progression angle on knee mechanics during an anticipated cutting task: A statistical parametric mapping approach - Peel, S. A.; Schroeder, L. E.; Weinhandl, J. T. (Journal of Biomechanics, 2022)
Cutting is considered a "high-risk" movement for anterior cruciate ligament (ACL) injuries. It has been established that sex differences exist during cutting, placing females at greater ACL injury risk. Foot progression angle (FPA) during landing has been shown to influence lower extremity mechanics, yet little is known how FPA influences mechanics during cutting. The purpose of this study was to compare two FPA conditions during cutting between males and females. Twenty-four males and females were tested using two FPA conditions: toe-in 15° (TI15) and toe-out 15° (TO15). Right knee joint kinematic and kinetic variables were measured using a motion capture system and force plate. Five successful trials were collected and compared between FPA conditions. One-dimensional statistical parametric mapping was used to assess changes in knee mechanics between males and females over the entire stance phase. The only sex × FPA effect found was knee flexion angle. Females cutting at TI15 had decreased knee flexion angle compared TO15 (p = 0.019). Significant sex main effects included knee abduction and rotation angles, and knee flexion and rotation moments. Significant FPA main effects included knee flexion, abduction and rotation angles. The results show cutting with a toe-in FPA of 15° is enough to induce changes in knee abduction angle while cutting with 15° toe-out FPA influenced knee flexion and rotation angles. These data suggest that different cutting FPAs may be influential on known ACL injury risk variables. However, more research is warranted on cutting FPA before FPA is targeted as part of ACL injury prevention protocols.